Joint report on social protection and social inclusion 2006 (Office for Official Publications of the European Communities, 2006)
Europe's policies on social protection and social inclusion face major challenges. Global competition, the impact of new technologies and an ageing population shape the long-term policy context. Weak growth, high unemployment and persistent inequalities need to be addressed in the short term. At Hampton Court in October 2005, the Heads of State and Government reflected on how Europe's social systems can be sustained in the face of such challenges and how they can contribute to meeting them. This second Joint Report on social protection and social inclusion responds directly to the challenges of the Hampton Court Summit and of Lisbon and builds on the 2003 Communication "Strengthening the social dimension of the Lisbon strategy: streamlining open method of coordiantion (OMC) in the field of social protection". It draws on the plans and policy statements produced by the Member States during 2005 under the three policy strands of social inclusion, pensions, health and long-term care.